Energikartläggning av Benzeliusskolan : Med investeringskalkyl för installation av bergvärme - Johansson, Alexander (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2018)
This thesis includes an energy survey of a school in Luleå called Benzeliusskolan and was carried out on behalf of the municipality of Luleå. Benzeliusskolan is currently heated with electric radiators and the thesis contains an investment calculation for the installation of a geothermal heating system. Calculations have been made to determine Benzeliusskolans theoretical heat demand. A survey of current electricity usage for heating has also been carried out for cost comparisons. The result of the thesis is following: • The theoretical heat demand for all buildings is 251 212 kWh per year. Transmission losses amount to 228 257 kWh and heat losses through infiltration amount to 34 646 kWh per year. The heat requirement for ventilation was calculated to 58 995 kWh. Heat input of 70 687 kWh takes place every year from internal heat and solar energy. • Mapping current consumption resulted in that current usage is 257 952 kWh of electricity for heating and 12 684 kWh of electricity for tap water per year. • The power requirement for all buildings, including waterborne heating batteries in all ventilation systems, was calculated to 146 kW. • A proposal for a geothermal heating system with a main central in house B where heat pumps are placed and heat transport to the other buildings, houses A and C, takes place through isolated culverts. The cost has been estimated at approximately 2 200 000 SEK through quotes and standard costs. The cost includes geothermal heat pumps, waterborne heating batteries for ventilation systems, drilling, radiators, installation costs and culverts between the buildings. The cost is based on an internal rate of 2% and an expected life span of 20 years. • The investment in a geothermal system results in a reduction in electricity consumption for heating and tap water of 68.8%, 186 275 kWh per year. The investment had resulted in a cost saving of approximately 113 000 SEK per year during the estimated 20-year life span of the heat pump. Break-even occurs after about 19 years and 7 months and ...